Job Satisfaction of Agricultural Professionals in Commercial Banks of Kerala - Suryaja, Vagvala; Thomas, Allan (Journal of Extension Education, 2020)
The study was conducted in Thiruvananthapuram district of Kerala, to analyse the factors affecting job satisfaction of agricultural professionals in commercial banks of Kerala. Ninety agricultural professionals working in two major banks viz., State Bank of India and Canara Bank were randomly selected. Ex-post facto research design was followed. It was found that about fifty per cent of respondents felt that they have high job satisfaction. The results of the Principal Component Analysis based on eigen values obtained revealed that all the five components viz., pay, promotion, work, supervision and people were the factors influencing job satisfaction.